A Perspective on the Behavior of Lithium Anodes under a Magnetic Field. Issue 1 (7th October 2020) - Yu, Linghui; Wang, Jiarui; Xu, Zhichuan J.
Abstract : Lithium metal‐based rechargeable batteries, such as lithium–sulfur and lithium–air batteries, are promising next‐generation batteries due to their high energy density. However, the use of lithium anode involves severe problems including poor cyclability and lithium dendrites‐related safety issues. It is reported recently that the presence of magnetic field can improve the cyclability and prevent the growth of lithium dendrites. However, it is unclear how, in detail, magnetic field affects lithium anodes. Herein, a competition relationship is proposed for understanding magnetic effect on lithium anodes. Magnetic field induces multiple magnetohydrodynamic (MHD) effects in a cell. These effects include an uneven current distribution across the electrode, enhanced mass transport, and redistribution of lithium ions around lithium dendrites. While the first effect promotes dendritic growth, the latter two benefit preventing their growth. Thus, the first competes with the latter two. Herein, it is shown that uneven current distribution can be the domain effect. It leads to earlier short circuits caused by dendrites and shortens the cycle life of lithium anodes through a higher electrolyte decomposition rate. As it appears to be an emerging approach to improve the performance of lithium anodes and rechargeable batteries using magnetic field, challenges and opportunities are discussed. Abstract : It is recently found very interesting to use magnetic field to overcome the issues of lithium anodes in rechargeable lithium metal batteries. However, it is not clear how, in detail, magnetic field affects lithium anodes. Herein, the effects of magnetic field on lithium anodes are discussed, in terms of mass transport, cyclability, lithium dendrite, and dendrite‐induced short circuit.